2018
DOI: 10.4273/ijvss.10.4.08
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Human Exposure to Vibrations using Quarter Car Model with Semi-Active Suspension

Abstract: Exposure of human body to vehicular vibrations in transit may lead to the human discomfort. Ride comfort is one of the major issues in design of automobiles. Magneto rheological (MR) dampers are emerging as most feasible solution for various applications in controlling vibrations. An MR damper is a semi-active device, which will offer the advantages of both active and passive suspension. In this study, the MR damper based semi-active suspension system for a car is analysed for ride comfort of 7 degrees of free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They compared skyhook, ground hook, and hybrid controllers and found that the hybrid controller outperformed the others in reducing vehicle body displacement and tire deflection, improving ride comfort. Ramasastry et al [13] investigated the ride comfort of a semi-active suspension system equipped with Magneto-rheological dampers by analyz-ing a human body mass model with seven degrees of freedom. The system significantly improved ride comfort compared to a passive damper system.…”
Section: Introductionmentioning
confidence: 99%
“…They compared skyhook, ground hook, and hybrid controllers and found that the hybrid controller outperformed the others in reducing vehicle body displacement and tire deflection, improving ride comfort. Ramasastry et al [13] investigated the ride comfort of a semi-active suspension system equipped with Magneto-rheological dampers by analyz-ing a human body mass model with seven degrees of freedom. The system significantly improved ride comfort compared to a passive damper system.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the test results, it was found that the determined values of the RMS index of accelerations recorded on the seat of a vehicle equipped with active suspension were lower than in the case of a vehicle with passive suspension. The article [34] analyzes the accelerations and longitudinal displacements of selected parts of the human body. The authors concluded that better driving comfort can be obtained by using a semiactive suspension.…”
Section: Introductionmentioning
confidence: 99%